Efecto de la aplicación de cataplasma de arcilla medicinal sobre el edema y dolor en el tratamiento de insuficiencia venosa periférica en extremidades inferiores en pacientes del centro de atención de medicina complementaria-red asistencial La Libertad-Essalud, enero-abril 2015 - Férnandez Sosaya, José Luis (2015)
The purpose of the current research was to evaluate the effectiveness of medicinal clay poultice, part of Geotherapy, in the symptomatic treatment of periferical insufficiency in lower limbs. Edema and perceived pain decrease has been evaluated. Patients who were diagnosed with minor chronic insufficienc :varicose veins were evaluated at medical practices at the “Centro de Medicina Complementaria” between January and April of 2015. Patients have been informed about this research and they were asked to sign an Evaluate – Consent form in order to obtain their unanimous approval. This research recruited 33 patients, it has accomplished the appropiate evaluation processes. Ressults have shown that applying medicinal clay as poultice shape caused an important reduction f pain in 32 patients (97% from total) and reduction of edema in 25 patients (75.75% from total) caused by the chronical venous insufficiency in lower limbs. To conclude, poultice of medicinal clay is effective to reduce pain caused by chronical venous insufficiency in lower limbs.